Effects of the burrowing mud shrimp, Upogebia yokoyai, on carbon flow and microbial activity on a tidal flat. Issue 3 (29th April 2014) - Sasaki, Akiko; Nakao, Hiroki; Yoshitake, Shinpei; Nakatsubo, Takayuki
Abstract: Mud shrimps, Upogebia spp., are major constituents of macrobenthic communities in tidal flats in Japan. The impact of Upogebia yokoyai on carbon flow on tidal flats was examined by comparing CO2 emission rates from plots with and without burrows in the Kurose River estuary, Japan. In situ CO2 emission rates from plots with burrows were significantly higher than from those without. Laboratory measurements using sediment core samples that excluded respiration of macrobenthic organisms showed similar trends. Although there were no significant differences in grain size distribution, water content, or ignition loss between the sediment cores with and without burrows, oxidation–reduction potential was significantly higher in sediment cores with burrows. Analysis of phospholipid fatty acids (PLFA) indicated that microbial biomass and community structure did not differ significantly between cores with and without burrows. However, microbial respiration activity, as indicated by CO2 emission rates per total PLFA content, was significantly higher in sediment cores with burrows than in those without. Our results indicate that burrows of U. yokoyai change the physicochemical conditions and increase microbial activity in the sediment, significantly affecting carbon flow in the tidal flat.